Do the Improved Water Sources for 203 Countries Converge over Time? - Chang, Yusang; Lee, Yootaek; Lee, Yoonji; Kim, Ki Bae (Journal of Environmental Accounting and Management, 2026)
The Sustainable DevelopmentGoals by the United Nations include a global target for Improved Water Source to reach 100% of population by 2030. There are still millions of people lacking the improved access to drinking water. We use the convergence methodology for 203 countries to determine whether the water shortage gap between water-rich versus water-poor countries has narrowed during 2000 to 2015. Results of our analysis show the narrowing of water shortage gaps. However, significant variations are found among income and regional subgroups. Implications of our findings indicate the reduction of water shortage gap within appropriate subgroups is needed. In particular, a set of policy recommendations are presented for sub Saharan Africa region where improvement of water supply is urgently needed.